Israi'liyyat dalam Pengajian Tafsir dan Sunnah - Hj. Sulaiman, Ishak (Jurnal Usuluddin, 1998)
Israi'liyyat is one of the important topics which discusses in the study of tafsir and sunnah. This article is focused on its definition, Historical issues, stand from Muslim faith and its implication in their way of life.